The appearance of the modern capitalist market and its effects on women’s agency. The loss of aura in Walter Benjamin - Valdés Lucas, Alicia (ENDOXA, 2021)
Historical processes imply different impacts on different historical agents. The processes that shaped the neoliberal capitalist market imposed the white heterosexual male as the only official agent of historical processes. This imposition was the basis for the construction of the current patriarchal system. This article asks how these historical processes affected women. How female agency has been conditioned by capitalism. This essay seeks to observe how the processes of consumption and mass production have affected the construction of female agency during the period of early capitalism. The conclusion is that this period needed to condition the construction of female agency by transforming it into patterns of consumption and production that meet the needs of the capitalist system itself.